Einflussfaktoren auf das Einnahmeverhalten von Analgetika bei Patient*innen mit chronischen tumorassoziierten Schmerzen: Eine qualitative Pilotstudie unter Berücksichtigung verschiedener Medikamentengruppen - Zugaj, Marco; Züger, Andrea; Keßler, Jens (Der Schmerz, 2023)
Background: Patients are surviving tumor diseases longer and longer due to the improvement of tumor-specific therapy and pain is a common symptom. The gold standard for tumor-associated chronic pain is multimodal therapy. Non-adherence causes high costs and may put patients at risk.The aim of this study was to investigate the adherence behavior and subjective treatment compliance of patients with tumor-associated chronic pain. The focus was on the patients' perspective. Different groups of medications, such as NOPA, opioids, co-analgesics and cannabinoids, as well as non-drug treatments were included.Methods: Semistructured guided interviews with 10 patients with chronic tumor pain were conducted within a qualitative research approach. The interviews were recorded and transcribed. The evaluation was using a focused content structuring interview analysis according to Kuckartz and Radiker.Results: Five main categories were defined. The central category based on the research question was "Adherence behavior from the patient's perspective." The category "Medication therapy" formed the framework of the study. Other main categories were "History of illness", "Relationship with treatment providers" and "Attitudes and beliefs". A total of 77 additional subcategories were formed and interpreted. Adherence behavior from the patients' perspective differed between the different medication groups. A palliative setting influenced treatment decisions and adherence. The medication regimens used were complex and dynamic, especially when there were multiple practitioners involved. Furthermore, there was ambiguity in the use of cannabinoids. Non-drug therapies were marginalized by patients. From the point of view of the patients interviewed, it was not so much the treatment providers who influenced their adherence behavior, but rather their own experiences, attitudes, and convictions.Discussion: The study included all medication groups and non-drug therapies equally, complementing previous literature in a qualitative setting. Adherence factors known from previous research were reflected in the subjective perception of the group of patients with chronic pain after tumor diseases. Marginalization of non-medication methods could be explained by the fact that multimodal therapy approaches were too rarely constantly used and controlled in the phase of chronification. Therefore, drug and non-drug therapies should be applied even more consistently to patients with tumor-associated pain.